IDENTIFIKASI DAN UJI AKTIVITAS SENYAWA TANIN DARI EKSTRAK DAUN TREMBESI (Samanea saman (Jacq.) Merr) SEBAGAI ANTIBAKTERI Escherichia coli (E. coli) - Puspita Sari, Putu; Susanah Rita, Wiwik; Puspawati, Ni Made (Jurnal Kimia (Journal of Chemistry), 2015)
Isolation and identification of tannin compounds from trembesi leaves ( Samanea saman (Jacq.) Merr) and its anti-bacterial activity test against Escherichia coli ( E. coli ) have been done in this research based on the utilization of trembesi leaves to treat diarrhea. Extraction was done by maceration and partition, separation by preparative TLC. The anti-bacterial activity was tested using wells that diffusion method, and the identification of the compounds was done with UV-vis spectrophotometer and FTIR. Maceration with ethanol produced 36.80 g crude ethanol extract. Phytochemical test showed that acetone and water fractions gave positive result for hydrolyzed tannin compounds but acetone fraction revealed more concentrated than water fraction. Anti-bacterial test result showed that the acetone fraction was active towards E.coli with medium activity. Separation of the eluent n-butanol: acetic acid: water (4:1:5) (BAA) gave six isolates but only two isolates (isolate 2 with Rf 0.61, and isolates 3 with Rf.0.65) gave positive results for tannin. These two isolates were relatively pure on TLC purity test and showed weaker anti-bacterial activity compared to the acetone fractions. Identification using UV-Vis spectrophotometer showed that isolates 2 and 3 gave two similar peaks with maximum absorbance at 346.50 nm and 347.00 nm respectively due to n? * and ?? * electron transitions, which indicated the presence of C=O  and C=C chromophores.  Infrared spectra of isolates 2 and 3 revealed peaks that correspond to characteristic functional groups of tannin including –O-H, C-H aliphatic, C=O esther, C=C aromatic, C-O-H, and C-O-C ether.
Keywords: Samaneasaman (Jacq.) Merr, tannin, antibacterial, Escherichia coli